Characteristics of optical limiting in media with nonlinear absorption and scattering - Zelensky, S.E.; Kolesnik, O.S.; Kopyshinsky, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
A comparative study is performed for characteristics of optical limiting in the media with nonlinear absorption and scattering with the use of nanosecond-scale laser pulses. Two methods are proposed to analyze of experimental nonlinear transmittance curves. The experiments revealed differences in the shape of nonlinear transmittance curves in the media with different physical mechanisms of optical limiting. For optical limiting in suspensions of light-absorbing particles, it is concluded that the fifth-order nonlinear susceptibilities should be taken into account.